Responses of the two‐spotted oak buprestid, Agrilus biguttatus (Coleoptera: Buprestidae), to host tree volatiles. Issue 4 (25th January 2016) - Vuts, József; Woodcock, Christine M; Sumner, Mary E; Caulfield, John C; Reed, Katy; Inward, Daegan JG; Leather, Simon R; Pickett, John A; Birkett, Michael A; Denman, Sandra
Abstract: BACKGROUND: Agrilus bigutattus (Fabricius) is a forest pest of increasing importance in the United Kingdom. The larvae damage weakened native oaks and are thought to contribute to premature tree death. Suspected links with acute oak decline (AOD) are not yet confirmed, but AOD‐predisposed trees appear to become more susceptible to A. biguttatus attack. Thus, management may be necessary for control of this insect. To explore the possibility of monitoring beetle populations by baited traps, the host tree volatiles regulating A. biguttatus –oak interactions were studied. RESULTS: Biologically active volatile organic compounds in dynamic headspace extracts of oak foliage and bark were identified initially by coupled gas chromatography–electroantennography (GC‐EAG) and GC–mass spectrometry (GC‐MS), and the structures were confirmed by GC coinjection with authentic compounds. Of two synthetic blends of these compounds comprising the active leaf volatiles, the simpler one containing three components evoked strongly positive behavioural responses in four‐arm olfactometer tests with virgin females and males, although fresh leaf material was more efficient than the blend. The other blend, comprising a five‐component mixture made up of bark volatiles, proved to be as behaviourally active for gravid females as bark tissue. CONCLUSIONS: These initial results on A. biguttatus chemical ecology reveal aspects of the role of attractive tree volatiles in the host‐finding of beetles and underpin the development of semiochemically based surveillance strategies for this forest insect. © 2015 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.